2015
DOI: 10.1371/journal.pone.0145724
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Mist1 Gene Expression Is Essential for Recovery from Acute Pancreatitis

Abstract: Acinar cells of the exocrine pancreas are tasked with synthesizing, packaging and secreting vast quantities of pro-digestive enzymes to maintain proper metabolic homeostasis for the organism. Because the synthesis of high levels of hydrolases is potentially dangerous, the pancreas is prone to acute pancreatitis (AP), a disease that targets acinar cells, leading to acinar-ductal metaplasia (ADM), inflammation and fibrosis—events that can transition into the earliest stages of pancreatic ductal adenocarcinoma. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 80 publications
3
32
0
Order By: Relevance
“…Several studies have shown that MIST1 is essential for appropriate responses to diverse cell stimuli, including alcohol and drug-induced inflammation, development, and response to secretagogues (9,10,12,26). Thus, we evaluated if induced Mist1 expression was restricted to ER stress conditions or whether other physiological stresses could influence expression of the Mist1 gene.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown that MIST1 is essential for appropriate responses to diverse cell stimuli, including alcohol and drug-induced inflammation, development, and response to secretagogues (9,10,12,26). Thus, we evaluated if induced Mist1 expression was restricted to ER stress conditions or whether other physiological stresses could influence expression of the Mist1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…Bioinformatics analyses also suggested that MIST1 regulates key genes during ER stress in response to activation of the IRE pathway. In order to examine this in greater detail, we took advantage of a newly developed Mist1 conditional mouse model where one Mist1 allele is flanked by loxP sites while the other Mist1 allele encodes CreERT2 (26). Tamoxifen-treated Mist1 CreERT/fl mice rapidly delete the remaining Mist1 coding allele, generating an acinar-specific Mist1 null pancreas.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations